Transnational organized crime in Latin America: Current trends and prospects for military crime-fighting operations - A. N. Pyatakov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Transnational organized crime (TOC) is among the most pressing new challenges to international security due to both its direct economic and social repercussions and the threat it poses to the very institution of the sovereign state. This problem is particularly acute in the countries of Latin America and the Caribbean (LAC), which are marked by exceedingly high rates of TOC activity and influence of cross-border criminal groups. This study identifies current trends in the development of TOC in the region, as well as the approaches of the Latin American countries to combating it. In the first section the author advances a hypothesis that TOC is not an anomaly, but an integral part and an attribute of globalization. From this point of view, cross-border criminal groups may be perceived as a specific kind of TNCs. The second section considers the key trends and specific features of organized crime development in LAC countries. The author shows that cross-border criminal groups and TNCs share a number of common traits. In particular, their activities contribute to the erosion of national sovereignty as they seek to oust states from their sphere of interests by both legal and illegal means. The third section examines the current approaches of LAC countries to combating cross-border criminal groups. The author emphasizes the growing role of the armed forces in fighting organized crime, and the increasing militarization of public security on the whole. On the one hand, this trend towards the ‘policialization’ of armed forces shows that the authorities of Latin American states recognize the threat posed by cross-border criminal groups. On the other hand, it indicates their inability to counter this threat effectively. The author concludes that the TOP problem is unsolvable within the existing system of public relations in LAC countries, since it is rooted in the very nature of the current model of globalization.